Recitation of Quran and its Relationship with Explanatory Reading: – A Study on the Impact of Recitation on Explanation – - Abdu, Abdulkareem Sharaf Mohammed (Journal of Islamic Sciences, 2022)
This study aimed to show the impact of recited reading of the Quran in explaining its meaning. This is known as the explanatory reading that is based on skill, good performance, and qualifying those who are specialized in teaching recitation according to the methodology of the ancestors in the teaching and accrediting of skillful readers of the Quran. The researcher used the inductive analytical and historical methodology in studying the punctuation made to the Quran. The most important results of the study are: the division of the Quran into parts and subparts does not comply with the reading of the verses in terms of their context, coherence, and cohesion. This calls for putting a term or symbol to be used in setting the beginning and end of the reading of the verses in the chapter (Surah) similar to the terms and symbols used in the setting of stopping and continuing of the verse.
Keywords: impact; intonation; performance skill; competence; interpreted reading